2013
DOI: 10.1080/09540253.2013.853028
|View full text |Cite
|
Sign up to set email alerts
|

Changing course: the gender gap in college selectivity and opportunities to learn in the high school curriculum

Abstract: Potochnick (2013) Changing course: the gender gap in college selectivity and opportunities to learn in the high school curriculum, Gender and Education, 25:7, 851-871,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Similar attention has been placed on the decreasing achievement of boys in academic areas [1,4] . Although boys outperform girls in standardized science and mathematics tests, girls are excelling in other areas of academic course taking.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…Similar attention has been placed on the decreasing achievement of boys in academic areas [1,4] . Although boys outperform girls in standardized science and mathematics tests, girls are excelling in other areas of academic course taking.…”
Section: Introductionmentioning
confidence: 95%
“…The National Student Clearinghouse (2015) [3] reported that bachelor degrees earned by women in science and engineering fields had decreased from 2004 to 2014. Further, researchers [4,5] have revealed that boys are more likely than girls to pass national high stakes examinations in mathematics and science. Boys were more likely than girls to achieve passing scores on ACT mathematics and ACT science exams [6] .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations